Do Institutions Cause Growth? Evidence from Asian Countries - Kharisma, Bayu; Wardhana, Adhitya; Sofyan, Mohammad Naufal Faisal (Jurnal Ekonomi & Studi Pembangunan, 2022)
A well-maintained political stability and economic freedom can encourage economic growth through investment, human capital, and technological developments. Adverse phenomena such as the Asia Rohingya conflict and uprisings in the Middle East conflict create an unstable political and economic environment, requiring institutions to develop an ideal environment for investors. This paper aims to identify the effect of political and economic institutions on economic growth. This paper uses panel data from developing Asian countries in 2009-2018 using the system GMM model. The results indicate that economic institutions have a positive and significant effect on economic growth. However, political institutions have no significant effect on economic growth. These results indicate that economic institutions have an essential role in maintaining and controlling the activities of emerging markets in Asia. Good institutions have to be in place to prevent fraud in market activities. In addition, economic freedom is one of the critical factors in attracting investment into the country to have a spillover effect on technological development.